Utilization of anionic polysaccharides to improve the stability of rice glutelin emulsions: Impact of polysaccharide type, pH, salt, and temperature. (March 2017) - Xu, Xingfeng; Luo, Liping; Liu, Chengmei; McClements, David Julian
Abstract: The objective of this study was to improve the physical stability of emulsions containing oil droplets stabilized by hydrolyzed rice glutelin (HRG) by coating them with anionic polysaccharides. Polysaccharide type and concentration had a strong influence on the properties of the coated droplets. Smaller particles with better pH-stability could be formed from xanthan gum or pectin than from alginate or gum arabic. The impact of environmental stresses on the stability of oil droplets coated with HRG-xanthan gum or HRG-pectin complexes was tested by measuring the impact of salt addition (0–500 mM NaCl, pH 3.5) and thermal processing (30–90 °C 30 min, 0 mM NaCl, pH 3.5). The emulsions containing xanthan gum were stable at all NaCl concentrations, whereas those containing pectin were only stable at low salt levels. Emulsions containing xanthan gum or pectin were stable to thermal processing. The improved stability of the emulsions containing the polysaccharides can be attributed to an increase in electrostatic and steric repulsion between the droplets. These results are useful for expanding the application of rice glutelin as a functional ingredient in the food industry. Graphical abstract: Highlights: Stability of hydrolyzed rice glutelin (HRG) emulsions is improved by adding polysaccharides. Pectin or xanthan gum gave better stability than alginate or gum arabic in HRG emulsions. Xanthan gum gave better salt stability than pectin in HRG emulsions. Xanthan gum gave better heat stability than pectin in HRG emulsions.